3D Hollow MoS2 Architecture Enabled Highly Sensitive SERS Detection - Chao Gao; Yi Yang; Huijie Chen; Xiaoqing Gao; Xingxing Zhang; Zhiqian Song; Tianyang Zhang; Kai Chen; Xiaohong Wang; Yingdong Han (Advanced Materials Interfaces)
Abstract Surface‐enhanced Raman spectroscopy (SERS) technology boasts merits of fingerprint recognition, a low detection limit, high sensitivity, and straightforward operation, and holds a significant position in the realm of molecular detection (even at the single‐molecule level). Recently, molybdenum disulfide (MoS2), as a special SERS substrate, has demonstrated various advantages like high molecular compatibility and an anti‐fluorescence background, thus emerging as a promising non‐metal substrate. Nevertheless, so far, how to improve and achieve SERS effects comparable to metal substrates remains a challenge for MoS2 based substrates. Therefore, this work presents and acquires a 3D hollow structured MoS2, which can be achieved through a simple hydrothermal method. Fortunately, the substrate achieves a detection limit of 10−8 M and an enhancement factor of 106 for rhodamine 6G (R6G) molecules, significantly improving the performance of the non‐noble‐metal MoS2 SERS. Theoretical analysis suggests that this should be attributed to the enhanced charge transfer between the substrate and probe molecules brought by the distinct monolayer self‐assembly and oxygen substitution in the 3D MoS2 architecture. The work provides a novel method to enhance the SERS performance of 2D materials, which is readily achievable and is expected to become a key cornerstone for the development of composite substrates.